Harry Potter and the Chamber of Secrets - Rowling, J. K.; GrandPre, Mary (New York : Arthur A. Levine Books, 1999)
When the Chamber of Secrets is opened again at the Hogwarts School of Witchcraft and Wizardry, second-year student Harry Potter finds himself in danger from a dark power that has once more been released on the school.
Sequel to: Harry Potter and the sorcerer's stone.
Elem. School Library Collection, June 2000.
School Library Journal starred, July 1999.
Notable/Best Books (A.L.A.), January 2000.
Booklist starred, May 1999.
Pub Weekly, May 1999.
Keywords: Potter, Harry, -- (Fictitious character) -- Juvenile fiction; Potter, Harry, -- (Fictitious character) -- Fiction; Hogwarts School of Witchcraft and Wizardry (Imaginary organization) -- Fiction; Wizards -- Fiction; Magic -- Fiction; Schools -- Fiction; Wizards -- Fiction; School stories; Magic -- Fiction; England -- Fiction